The Legislative Evolution of Court Jurisdiction over Cases Involving Ministries and Government Entities - Munira Mohammed Salem Rahma (Journal of Legal Sciences, 2024)
The jurisdiction over disputes involving federal entities and ministries in the United Arab Emirates has evolved through several legislative stages. Initially, according to the procedural legislation, jurisdiction over such disputes was assigned to the comprehensive circuit of the primary court, regardless of the subject matter's value. Subsequently, an amendment allocated jurisdiction to the comprehensive circuit of the Federal Primary Court in the Emirate of Abu Dhabi, with the potential for the same court in other emirates to handle disputes involving federal entities and ministries. Following the repeal of previous legislation and the enactment of the new procedural law, No. 42 of 2022, exclusive subject matter jurisdiction for disputes involving federal entities and ministries was conferred upon the Federal Primary Court in the Emirate of Abu Dhabi, designating it as the sole competent court for these disputes. This legislative evolution, has led us to address this topic in two sections: The first section examines jurisdiction over disputes involving ministries and federal entities prior to the issuance of Federal Decree-Law No. 42 of 2022. The second section explores jurisdiction over these disputes under Federal Decree-Law No. 42 of 2022. At the conclusion of the study, we will propose a set of recommendations as legislative solutions to the UAE procedural legislator, based on our analysis of the legislative texts reviewed.